EFFECTIVENESS ON GROUND MARKETINGIN JAPANESE COURSE INSTITUTIONS - HetyNurohmah; NadhiraArifah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Mapping the promotion strategy in particular at a relatively new course is a very important thing to do. How can the promotion strategy carried out be effective and efficient. The purpose of this paper was to determine the effectiveness of the promotion strategy at one of the Japanese language course institutions and the level of success of the follow-up promotions carried out. The author uses a descriptive method which is a method for making reports through direct observation in the field and collecting data from promotional activities carried out at one of the Japanese language course institutions. The data used by the authors are prospective consumer data obtained from February - April 2018. The conclusion of this paper is the implementation of the strategy on ground marketing by holding events and conducting street marketing followed by follow-up in the form of sales calls and mobile marketing is successful. The highest level of success is achieved with a follow-up sales call. The highest interest is students. The area of promotion with the most interest is in the university environment.